Les fantômes d’Isaac Babel : aux confins du texte et de la mémoire - Nicolas Aude (Carnets, 2023)
This article aims to examine the notion of phantom text and its relevance in the construction of the comparative object. To do this, it takes as object the exemplary work of the Russian-speaking Jewish writer from Ukraine Isaac Babel, focusing more particularly on its reception. In the case of this cosmopolitan author, the metaphor of the ghost evokes both the attachment to the city of Odessa, the fragmentation of his narrative work and the memory of a deeper cultural loss caused by the disappearance of the writer’s manuscripts following his arrest by the NKVD in 1938. The article then shows how the lack of archive generates new texts but also images (in cinema and comics) which, in turn, question the relationship between fact and fiction and the ambiguities of Babel’s internationalist utopia.